2017
DOI: 10.3856/vol45-issue4-fulltext-17
|View full text |Cite
|
Sign up to set email alerts
|

Response of mangrove propagules to the presence of oil and hydrocarbon degrading bacteria during an experimental oil spill

Abstract: ABSTRACT. The aim of this work was to investigate the effect of marine diesel oil on the development and survival of three different species of mangrove propagules with or without a hydrocarbon-degrading bacterial consortium and the possible use of propagules for the recovery of mangroves impacted by oil. The study was conducted in a greenhouse, near a mangrove from which we collected samples of sediments and propagules of Laguncularia racemosa, Avicennia schaueriana and Rhizophora mangle. The bacterial consor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Chequer et al [ 44 ] observed the same pattern in the esterases and dehydrogenases enzyme activities on impacted soil by diesel oil, maintaining the number of cells in sediments. The same activity pattern was also observed in sediments from Guanabara Bay, Brazil, due to contamination by Cu, Zn and Pb [ 45 , 52 ].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Chequer et al [ 44 ] observed the same pattern in the esterases and dehydrogenases enzyme activities on impacted soil by diesel oil, maintaining the number of cells in sediments. The same activity pattern was also observed in sediments from Guanabara Bay, Brazil, due to contamination by Cu, Zn and Pb [ 45 , 52 ].…”
Section: Discussionmentioning
confidence: 81%
“…Several studies have used dehydrogenase activity as a marker of toxicity of petroleum hydrocarbons, pesticides, and metals to soil and sediment bacteria [ 5 , 44 51 ]. In our study, the parameters of esterases and dehydrogenases activities demonstrated, respectively, a pattern for the hydrolysis of biopolymers and intracellular supply with compounds <600 Da [ 32 ] for energy production, sufficient to maintain the number of cells.…”
Section: Discussionmentioning
confidence: 99%
“…The abundances of most of the dominant diesel-oil-degrading bacteria increased after the immobilization on MAC, such as Pseudomonas, Bacillus, Microbacterium, Staphylococcus, Luteimonas and Caulobacter. For instance, the Brevundimonas was demonstrated to be a main degrading bacteria of diesel oil [29], and its abundance increased from 53.67 to 58.34% after immobilization. Pseudomonas, Bacillus, Rhodococcus and Microbacterium all have petroleum hydrocarbon degradation capability [30], the abundance levels of which increased by 9.07% compared to the free culture condition.…”
Section: Changes In Community Structures Of Degrading Bacteria After ...mentioning
confidence: 99%
“…The impact of oil on coastal environments depends on the amount of spillage, the type of oil and its toxicity, and environmental conditions such as the predominant type of sediments, tidal circulation and prevailing climatic conditions at the time of contact with the oil (Soares et al 2006;Chequer et al 2017). Acute and chronic effects result from impacts of different types of oil in mangrove ecosystems (Hoff and Michel 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is in this highly vulnerable phase of the plant that the presence of tensors in the water can affect germination. Oil contamination can harm the germination process, as well as the growth, development and establishment of mangrove seedlings (Duke et al 1998;Chindah et al 2011;Hoff and Michel 2014;Chequer et al 2017).…”
Section: Introductionmentioning
confidence: 99%